Properties of mortar with waste tyre rubber as partial sand replacement - Chong, Beng Wei; Rokiah, Othman; Tan, Wei Sheng; Putra Jaya, Ramadhansyah; Mohd Mustafa Al Bakri, Abdullah (Trans Tech Publications, Switzerland, 2021)
Around 1000 million waste tyres are generated annually and over 5000 million more are estimated to be discarded by 2030. It is estimated that one waste tyre is discarded per person in developed areas; hence 1 billion waste tyres are disposed worldwide. Waste tyre is difficult to manage as it takes up space, is difficult to compress and combustion of tyre releases highly toxic substance into the air. Hence, most of them end up in the landfill, as past research data estimated that currently 4 billion waste tyres can be found in landfills. In this study, up to 30% tyre rubber with a fine grind size of 300nm to 500nm was used as partial sand replacement in type N cement mortar. The rubber was treated with 1M NaOH solution to enhance its ability to bond with the other constituent materials. Tests were conducted to determine the properties of rubberised mortar, including consistency, compressive strength, flexural strength, water absorption and acid attack. From the test result, tyre rubber reduced the consistency and strength of mortar. Mathematical regression model showed that reduction of strength occurred in a second-order polynomial function with percentage of rubber. It was concluded that at up to 20% replacement rubberised mortar has the best resistance against water absorption and acid attack while still achieving the target strength.